Fenomena Hijrah Kontemporer Di Indonesia: Konstruksi Sosial Pengetahuan Keagamaan Di Era Digital - Fikri Maulyda (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article examines the contemporary hijrah phenomenon in Indonesia with a focus on three main aspects: (1) the transformation of the production and distribution of religious knowledge through social media, (2) the construction of urban middle-class religious identity, and (3) the paradox between spirituality and consumerism. Using Peter Berger's theoretical framework on the social construction of reality and the theory of the democratization of religious authority, this article shows that hijrah is a complex phenomenon that reflects the negotiation of Indonesian Muslim identity in the digital era. The findings reveal that social media has created a new ecosystem in the production of democratic yet fragmented religious knowledge, while the hijrah movement paradoxically integrates spiritual values ​​with modern consumerist practices.